3D GPR survey for the archaeological characterization of the ancient Messapian necropolis in Lecce, South Italy. (June 2016) - Leucci, G.; De Giorgi, L.; Di Giacomo, G.; Ditaranto, I.; Miccoli, I.; Scardozzi, G.
Abstract: Extensive urbanization may cover important archaeological structures that are still buried in urban areas, and Ground Penetrating Radar is one of the most reliable geophysical technique for resolving buried archaeological structures in urban territories. In this paper a case study that involves a geophysical survey employing the surface three-dimensional (3D) GPR techniques, to characterize the investigated areas from the archaeological point of view, is illustrated. GPR measurements, integrated with archaeological and topographical information aimed at the production of a digital archaeological map integrated in a webGIS platform, were carried out in some areas at the historical centre of Lecce (Apulia, Italy). The investigated areas are related to some sectors of the Messapian necropolises (dated mainly in 4th–3rd century BCE), characterized by different types of graves (pits dug in the bedrock or built with slabs, sarcophagi and hypogea) that lying also inside the settlement surrounded by city walls. The survey was carried out using the IDS Hi Mod georadar system, incorporating a dual band 200–600 MHz centre frequency antennae. The GPR time slices were constructed from closely spaced parallel profiles. The time slices, computed from averaging radar reflections over vertical time windows several nanoseconds thick, are used to map subsoil features associated with its structure. The time slices were georeferenced in the archaeological map of Lecce in order to acquire new data on the distribution and the ancient topography of the funerary areas inside the settlements. Moreover, to facilitate the interpretation of the results, a three-dimensional image was constructed using closely spaced parallel profiles, which are interpolated. Highlights: Methodological approach Urban archaeological map 3D reconstruction of archaeological structures by GPR data